Peningkatan Kemampuan Literasi dan Numerasi Matematika Melalui Pondok Literasi - Alfonsa Maria Abi; Demeryati Langtang; Dyen Erni Lakapu; Anggreni Beatrix Liunokas (Abdimas Mandalika, 2026)
Abstract:  Mathematical numeracy literacy is the ability to analyze and understand statements through the activity of manipulating symbols/language found in everyday life and expressing these statements in writing/orally. AKM as a student suitability test in the field of literacy and numeracy, orients the learning process towards increasing literacy and numeracy since elementary school (SD). However, in reality, there are still many SD who have not fully addressed this challenge, which leads to low mathematical numeracy literacy skills. One of them is in Desa Benlutu, Kecamatan Batu Putih, Kabupaten TTS. Therefore, efforts were made to improve mathematical numeracy literacy skills through literacy huts. This activity was carried out by lecturers and students of the Institut Pendidikan Soe in collaboration with the Desa Benlutu government with three SD (SD GMIT Benlutu, SD Inpres Oenunuh, and SDK Yaswari Benlutu). This activity improved the mathematical numeracy literacy skills of elementary school students. Evaluation results showed an increase in students' literacy skills, including the application of number concepts to the area and perimeter of flat shapes, the use of numbers in arithmetic operations, and contextual problem solving. This activity had a positive impact on students, teachers, and the local community, improving students' mathematical numeracy literacy.Abstrak: Kegiatan Pengabdian kepada Masyarakat (PkM) ini bertujuan untuk meningkatkan kemampuan literasi numerasi matematika siswa Sekolah Dasar (SD). Kegiatan ini dilaksanakan oleh dosen dan mahasiswa KKNT Institut Pendidikan Soe bekerja sama dengan pemerintah desa Benlutu dan 3 (tiga) sekolah dasar di Desa Benlutu (SD GMIT Benlutu, SD Inpres Oenunuh, dan SDK Yaswari Benlutu). Metode pelaksanaan kegiatan meliputi perencanaan, persiapan, pelaksanaan, evaluasi dan pelaporan. Kegiatan PkM ini berhasil meningkatkan kemampuan literasi numerasi matematika siswa. Hasil evaluasi memperlihatkan peningkatan kemampuan literasi siswa mencakup penerapan konsep bilangan pada luas dan keliling bangun datar, penggunaan bilangan dalam melakukan operasi aritmatika, serta penyelesaian masalah kontekstual. Kegiatan ini berdampak positif bagi siswa, guru, dan masyarakat setempat bagi peningkatan literasi numerasi matematika siswa.